Pengaruh Kinerja ESG terhadap Manajemen Laba Riil: Peran Moderasi Kepemilikan Kas - Sriwijayanti, Irma; Septiani, Delina Herdian; Rahmani, Hani Fitria; Mauludina, Muhammad Alam; Tampubolon, Ricky Brian D.P. (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to investigate the influence of Environmental, Social, and Governance (ESG) performance on real earnings management (REM) practices, with cash holdings acting as a moderating variable, in non-financial companies listed on the Indonesia Stock Exchange (IDX). The research employs a quantitative approach with purposive sampling, yielding 90 firm-year observations from companies that disclosed complete ESG scores between 2021 and 2023. The data were analyzed using panel data multiple linear regression to test the proposed hypotheses. The findings reveal that higher ESG performance is negatively and significantly associated with real earnings management, indicating that companies with stronger sustainability commitments are less likely to engage in REM practices. However, cash holdings were found not to moderate the relationship between ESG performance and REM, suggesting that liquidity alone does not influence the effectiveness of ESG in curbing earnings manipulation. These results underscore the importance of ESG as a mechanism for enhancing financial reporting quality and corporate transparency. They also offer practical implications for investors, regulators, and other stakeholders, encouraging them to view ESG metrics not only as indicators of sustainability but also as proxies for corporate ethical behavior and integrity in financial disclosures.